Status of Snow Leopard (Uncia uncia) in Humla District, Western Nepal - Khatiwada, JR; Ghimirey, Y (Scientific World, 2010)
This study was carried out in the Humla District, West Nepal during April - May 2007. The Snow Leopard Information Management System, SLIMS (second order survey technique) developed by International Snow Leopard Trust was used to determine the status of snow leopard in the area. Altogether, 13 transects (total length of 6.76 km) were laid down in the major two blocks of Humla. A total of 45 snow leopard's Signs (32 scrapes, 11 feces, 1 urine mark and 1 pugmark) were recorded. Fixed-point count from method was used for blue sheep survey from appropriate vantage points. Interviews were conducted to find out relevant information on livestock depredation patterns and locals perception towards snow leopard. Out of 12 households surveyed in the area, 60% of herders lost livestock due to snow leopards. A total of 16 animals were reportedly lost due to snow leopards in 2007. High retaliatory killing and poaching are the major threat to the species in the area. Therefore, long-run survival of the species seems uncertain in the area. Habitat disturbance and over grazing have disturbed the prey species and ultimate impact on snow leopard. More awareness and income generation programs are needed to make the locals aware about the role of predator in the ecosystem. Key words: Snow leopard; Prey species; Status; Humla; Conflict. DOI: 10.3126/sw.v7i7.3825 Scientific World Vol.7(7) 2009 pp.49-52